2010
DOI: 10.1681/asn.2009070698
|View full text |Cite
|
Sign up to set email alerts
|

ZONAB Promotes Proliferation and Represses Differentiation of Proximal Tubule Epithelial Cells

Abstract: Epithelial polarization modulates gene expression. The transcription factor zonula occludens 1 (ZO-1)-associated nucleic acid binding protein (ZONAB) can shuttle between tight junctions and nuclei, promoting cell proliferation and expression of cyclin D1 and proliferating cell nuclear antigen (PCNA), but whether it also represses epithelial differentiation is unknown. Here, during mouse kidney ontogeny and polarization of proximal tubular cells (OK cells), ZONAB and PCNA levels decreased in parallel and invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 44 publications
3
105
0
1
Order By: Relevance
“…12,13 In addition to defective apical transport, abnormal proliferation is often observed in diseased PT cells. 13,24,33 Increased proliferation was consistently observed in kCH kidneys and mPTCs exposed to RFS-kLCs as indicated by the PCNA and cyclin-D1 markers and bromodeoxyuridine incorporation. Our data suggest the involvement of the Y-box transcription factor ZONAB, which is active during nephrogenesis and PT maturation.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 In addition to defective apical transport, abnormal proliferation is often observed in diseased PT cells. 13,24,33 Increased proliferation was consistently observed in kCH kidneys and mPTCs exposed to RFS-kLCs as indicated by the PCNA and cyclin-D1 markers and bromodeoxyuridine incorporation. Our data suggest the involvement of the Y-box transcription factor ZONAB, which is active during nephrogenesis and PT maturation.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that ZONAB and ZO-1 are part of a pathway by which TJs can regulate epithelial cell proliferation [33]. ZONAB is a Y-box transcription factor that binds to the ZO-1 SH3 domain and modulates the expression of genes encoding proteins involved in differentiation and cell proliferation in normal epithelial [34] and uveal melanoma cells [35]. Both proteins, after specific stimulus, localize in the nucleus and bind to specific promoters containing an inverted CCAAT box (Y-box).…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation before atrophy implies reversal of the apical differentiation program and might account for asynchrony between individual apical components as reported in cultured PTCs. 18 Long considered as degradative organelles, lysosomes emerge as signaling compartments that are able to impact on gene expression. 37 The signaling and transcriptional linkages between lysosomal expansion before crystals and repressed apical differentiation before atrophy deserve additional studies.…”
Section: Explanation Of Fanconi Syndrome and Swan-neck Lesionsmentioning
confidence: 99%
“…17 However, as shown in polarized PTCs cultures, expression of apical endocytic receptors strongly depends on differentiation state. 18 To address these issues, we exploited congenic Ctns 2/2 C57BL/6 mice, 5 which allowed us to study early kidney events that are inaccessible in patients. This established model shows (1) high cystine levels, , and RBP in one WT and two Ctns 2/2 mice (#1 and #2) in serial collections at the indicated ages (loads normalized to 2 mg creatinine).…”
mentioning
confidence: 99%